مستوى التفكير الإبداعي لدى تلاميذ الصف الرابع الأساسي (دراسة ميدانية في محافظة اللاذقية) - جناد روعة; علي خضر; صالح لارا (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدف البحث إلى معرفة مستوى التفكير الإبداعي بمهاراته (طلاقةً، مرونةً، أصالةً، إبداعاً كلياً) لدى تلاميذ الصف الرابع الأساسي في محافظة اللاذقية تبعاً لمتغير الجنس. ولتحقيق هذا الهدف استخدمت الباحثة اختبار تورانس للتفكير الإبداعي صورة الألفاظ (أ)، تكونت العينة من(255) تلميذاً وتلميذة 125) ذكراً و130 أنثى). تم اختيارهم بطريقة عشوائية من عدة مدارس في محافظة اللاذقية، وأظهرت النتائج ضعف مستوى التفكير الإبداعي لدى تلاميذ الصف الرابع الأساسي في محافظة اللاذقية، وكان متوسط الدرجات على الشكل التالي: (الإبداع الكلي95.21، الطلاقة46.85، المرونة28.27، والأصالة20.08)، كما أظهرت النتائج عدم وجود فروق ذات دلالة إحصائية في كل من مهارات التفكير الإبداعي (طلاقة– أصالة – إبداع كلي) تعزى لمتغير الجنس، ووجود فروق ذات دلالة إحصائية في درجة المرونة لصالح الإناث. وفي ضوء النتائج أوصى البحث بضرورة دمج مهارات التفكير الإبداعي في مناهج التعليم الأساسي، وتدريس هذه المهارات بشكل مستقل، وضرورة عقد دورات تدريبية مطورة للمعلمين لتدريبهم على كيفية تنمية التفكير الإبداعي لدى الطلبة في أثناء تدريسهم الصفي، وضرورة بناء اختبارات لقياس مهارات التفكير الإبداعي مقننة على البيئة السورية، وإجراء المزيد من الأبحاث حول موضوع التفكير الإبداعي( من حيث قياس مستواه وتنميته) في مراحل دراسية أخرى وفي ضوء متغيرات أخرى. The research aimed to identify the level of creative thinking skills (fluency, flexibility, originality, whole degree) among basic fourth class students in Latakia, in the light of gender. To achieve this purpose, the researcher used Torrance test of creative thinking-vocabulary form (A). The sample consisted of (255) students (125 males and130 females)selected by using random sampling method, from several schools in Latakia, The results showed weakness in the level of creative thinking among basic fourth class students. The average of degrees were(the whole degree95.21, fluency 46.85, flexibility 28.27,and originality 20.08), The results also showed that there were no statistically significant differences in each skill of creative thinking (fluency, originality, and whole degree) due to gender, but there were statistically significant differences in degree of flexibility in favor of females. In the light of the findings, the study suggested merging the skills of creative thinking in curriculum, and teaching these skills independently, fasten training session to teachers to habituation them on development of creative thinking during the class teaching, and setting up tests to measure creative thinking skills codified in Syrian environment, and conducting new researches focusing on creative thinking (from where measuring and development him) in different school levels, with using other variables.